Hubungan Tempat Penampungan Air Buatan dengan Keberadaan Jentik Aedes aegypti di Dusun Kebonagung Desa Tridadi Kecamatan Sleman Kabupaten Sleman - Novita Sekarwati (Poltekkes Kemenkes Yogyakarta, 2017)
The very low ABJ in Kebonagung Hamet (5,26 %) compared to national number (95 %) is influenced by several factors, such as: behavior of collecting water for daily need not only in one place, and water storage that is rarely cleaned. The purpose of this research was to understand the relationship between artificial water containers and the existence of Aedes aegypti larva in Kebonagung Hamlet of Tridadi Village, Sleman District, in Sleman Regency. The method used was analytic observational with cross sectional approach. The 106 sample houses were selected by following simple random sampling technique. The data were obtained by using a check-list and several other supportive devices for larva examination. The study results find that there were 12 artificial water containers which were positive of Aedes aegypti larva (House Index 11,32 %). The statistical test using Fisher’s Exact at 95 % level of significance, reveals that artificial water conatiners correlates with the existence of Aedes aegypti larva (p-value < 0,01). The logistic regression test obtained the value of Exp (B)= 0,128; which means that every artificial water container would increase the risk of Aedes aegypty larva existence by 0,128 times.